Employment at 55+: Do We Want to Work Longer in Lithuania? - Zitikytė, Kristina (Ekonomika, 2020)
The Lithuanian population is aging, and it causes many difficulties for public finances by increasing expenditures on health care, long-term care, and pensions, and also for the labor market by creating labor shortages. One of the ways to cope with demographic aging is to rise the employment rate of older people. According to Eurostat, the employment rate of the elderly aged 55–64 years increased from 49.6 percent in 2005 to 68.5 percent in 2018 in Lithuania and it is higher than the average employment rate of older workers in European Union, which was 58.7 percent in 2018. This paper focuses on older people in Lithuania, aged 55 and over, trying to answer a question whether the elderly in Lithuania willingly work or try to find alternatives such as receiving long-term social insurance benefits. The research findings show that the activity of older people in the labor market grows, and even the share of people with disabilities staying in the labor market increases. However, this analysis also shows that older people are more under risk to lose their job during an economic crisis, and this suggests that trying to find work alternatives can be closely related to one’s economic situation. Moreover, health problems remain one of the main factors limiting the activity of older people in the labor market. It is also noticeable that some labor force reserves exist among people with disabilities and this supposes that creating better adapted working conditions for older and disabled workers in Lithuania could probably contribute to meeting the needs of an aging workforce.